Quantitative Techniques: Theory & Problems - TULSIAN PANDEY & VISHAL PANDEY (Chennai., Pearson India, 2022)
This book adopts a fresh and novel approach to the study of Quantitative Techniques and provides a comprehensive coverage of the subject. Essentially designed for extensive practice and self-study, this book will serve as a tutor at home. Chapters contain theory in brief, numerous solved examples and exercises with exhibits and tables.
Keywords: MBA; Quatitative Techniques